TANTANGAN DAN PELUANG PEMASARAN DESA WISATA BEDULU DALAM KONSEP VIRTUAL TOUR 360o MENUJU ERA DIGITALISASI 5.0: KASUS DESTINASI WISATA CANDI TEBING TEGALLINGGAH, GIANYAR, BALI - Yuda, Ida Bagus Nyoman Krisna Prawira; Patrinang, Emilia Eka; Rande, Florin Fatika Sari Pade; Mamulak, Maria Sonya Lotu (Journal of Hospitality Accommodation Management (JHAM), 2025)
This study investigates the implementation of 360-degree virtual tours as a marketing promotion strategy for rural tourism destinations within the Industry 5.0 paradigm. Focusing on the Tegallinggah Cliff Temple in Bedulu Village, Gianyar, Bali, the research specifically explores the marketing strategies employed, alongside the concomitant challenges and opportunities arising in this advanced digital era. Adopting a qualitative methodology, data were collected through focus group discussions, observations, and document analysis. Findings indicate that the destination management employs several key strategies: collaboration with the Bali Tourism Directory website, provision of specialized training and development programs in digital tourism marketing, and strategic allocation of budgets for essential digital infrastructure. The study concludes that 360-degree virtual tour promotion significantly enhances destination visibility and appeal for both domestic and international tourists. Furthermore, the research identifies critical implications and provides actionable recommendations for tourism practitioners to optimize digital marketing management and strategic planning for the Tegallinggah Cliff Temple destination.